Kognitywna definicja Welesa Wołosa: Etnolingwistyczna próba rekonstrukcji fragmentu słowiańskiego tradycyjnego mitologicznego obrazu świata Cognitive Definition of Weles Wołos: An Attempt at Reconstruction of a Fragment of the Traditional Mythological Appearance of the Slavic World - Łuczyński, Michał (Studia mythologica Slavica, 2012)
<span style="line-height: 115%; font-family: ’Calibri’,’sans-serif’; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: ’Times New Roman’; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">The author analyses Weles Wołos, a supreme »Cattle-God« in Old-Slavic pagan religion and mythology, which is correlated to poetry, magic and cattle. The author focuses on that problem as a part of Slavic mythology worldviews.